Partner violence victimization and unintended pregnancy in Latina and Asian American women: Analysis using structural equation modeling. Issue 4 (21st April 2017) - Cha, Susan; Masho, Saba W.; Heh, Victor
ABSTRACT: Intimate partner violence (IPV) is a pervasive public health problem in the U.S., affecting nearly one in every three women over their lifetimes. Using structural equation modeling, we evaluated the association between IPV and unintended pregnancy, mediated by condom use and perceived spousal/partner support among Latina and Asian women. Data came from the 2002–2003 National Latino and Asian American Study (NLAAS). The analysis was restricted to married or cohabiting female respondents aged 18+ years ( n = 1, 595). Dependent variables included unintended pregnancy, condom use, and perceived partner support. Independent variables included physical abuse or threats by current partner and primary decision-maker. Weighted least squares was used to fit path models to data comprising dichotomous and ordinal variables. More than 13% of women reported IPV during their relationship with their partner/spouse. Abused women were twice as likely as non-abused women to have had an unintended pregnancy. This association was partially mediated by perceived partner support. Condom use had a positive, but non-significant association with unintended pregnancy, and IPV had a negative, but non-significant association with condom use. Results highlight the importance of IPV screening for minority women. Efforts to combine family planning and violence prevention services may help reduce unintended pregnancy.